2002
DOI: 10.1001/archinte.162.18.2053
|View full text |Cite
|
Sign up to set email alerts
|

Medical Complications and Outcomes After Hip Fracture Repair

Abstract: Most patients had no medical complications after hip fracture repair. Serious cardiac and pulmonary complications were equally important in frequency, mortality, and survivors' length of stay. Patients with multiple complications had especially poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
202
7
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(229 citation statements)
references
References 54 publications
12
202
7
8
Order By: Relevance
“…In a retrospective study including 8,930 patients operated for a hip fracture, medical complications occurred in 19% (Lawrence et al 2002). Cardiac and pulmonary complications were most frequent.…”
Section: Complicationsmentioning
confidence: 99%
“…In a retrospective study including 8,930 patients operated for a hip fracture, medical complications occurred in 19% (Lawrence et al 2002). Cardiac and pulmonary complications were most frequent.…”
Section: Complicationsmentioning
confidence: 99%
“…5 High complication and mortality rates associated with hip fractures have been well documented in the literature. [6][7][8][9][10][11][12][13][14][15] Poor outcomes may be predicted by patient comorbidities, surgical timing, and surgical volume. 7,[15][16][17][18][19][20][21][22][23][24][25][26][27] The effect of surgical time of day on hip fracture outcome is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…PPCs are common and contribute to increased length of stay, perioperative morbidity, and mortality [13, 14]. It has been reported that pulmonary complications affected 4% of patients after hip fracture repair, and more than half of them were severe complications, such as pneumonia or respiratory failure [15]. A growing body of evidence indicates that PPCs may even predict long-term survival, especially among patients aged 70 or above [16, 17].…”
Section: Introductionmentioning
confidence: 99%